Analysis of the Transformation of Ethnic Entrepreneurship: Processes and Features of Research on the Business of Kore Saram (Journal of Oriental Studies, 2023)
In this paper, the authors reveal the discourse of ethnic entrepreneurship on the example of English-language literature. Practical studies of ethnic entrepreneurship on the example of the diasporas of the CIS countries have shown Russian-language academic works. The authors found that on the materials of the ethnic community of the dynamically developing Kazakh society of entrepreneurs, studies were not noticed in a significant amount. In this regard, there is a need to study the general and particular aspects of ethnic entrepreneurship on the example of the Korean business of Kazakhstan. The importance of alternative research strategies was pointed out by many scientists, the authors of this work paid attention to the qualitative method of analysis. Using the example of a qualitative analysis of interviews with ethnic businessmen of the young Korean generation, the authors drew a parallel with the peculiarities of the ethnic business of the first generation of Korean entrepreneurs, who demonstrated adherence to the enclave theory in entrepreneurship. The generation of Korean businessmen of the 2000s is the generation of ethnic entrepreneurship of a new format. The object of consideration was the Association of Korean Business Clubs (OKBC) as an example of an innovative approach to managing business processes throughout the CIS. Having revealed the “portrait of a businessman” of the post-Soviet period, the authors obtained the features of ethnic business in the form of three components: innovation, internationalization, and the preservation of ethnic culture.